Does Family Environment Moderate The Effect of Financial Literacy, Attitudes and Motivation on Investment Interest - Yuniningsih Yuniningsih; Bowo Santoso (Atestasi : Jurnal Ilmiah Akuntansi, 2020)
Investment interest is the desire to invest, which is followed by a lot of information seeking. Everyone, including a lecturer, may be interested in investing in any form, either real assets or financial assets. Investments are made to obtain a benefit in the future. This research aims to determine how a lecturer's behavior in fostering interest in investing in financial assets, especially stocks, considers the factors that influence it. Participants in this study were lecturers in Surabaya who were certified lecturers and were permanent lecturers at public and private universities. This study uses three exogenous latent variables consisting of financial literacy, attitude, and motivation. One endogenous latent variable, namely investment interest and one moderating variable, namely family. Of the five variables used measured by a total of 21 indicators. The participants in this study were 103 participants. The participants in this study were 103 participants. This study indicates that the variables of financial literacy and motivation have a significant influence on the interest in investing in financial assets. This study suggests that financial literacy and inspiration variables have a considerable impact on the interest in investing in financial assets.